The effect of isohydric hemodialysis on the binding and removal of uremic retention solutes. - Aleksey Etinger; Sumit R Kumar; William Ackley; Leland Soiefer; Jonathan Chun; Prabjhot Singh; Eric Grossman; Albert Matalon; Robert S Holzman; Bjorn Meijers; Jerome Lowenstein (PLoS ONE, 2018)
BACKGROUND:There is growing evidence that the accumulation of protein- bound uremic retention solutes, such as indoxyl sulfate, p-cresyl sulfate and kynurenic acid, play a role in the accelerated cardiovascular disease seen in patients undergoing chronic hemodialysis. Protein-binding, presumably to albumin, renders these solutes poor-dialyzable. We previously observed that the free fraction of indoxyl sulfate was markedly reduced at the end of hemodialysis. We hypothesized that solute binding might be pH-dependent and attributed the changes in free solute concentration to the higher serum pH observed at the end of standard hemodialysis with dialysis buffer bicarbonate concentration greater than 35 mmol/L. We observed that acidification of uremic plasma to pH 6 in vitro greatly increased the proportion of freeIS. METHODS:We tested our hypothesis by reducing the dialysate bicarbonate buffer concentration to 25 mmol/L for the initial half of the hemodialysis treatment ("isohydric dialysis"). Eight stable hemodialysis patients underwent "isohydric dialysis" for 90 minutes and then were switched to standard buffer (bicarbonate = 37mmol/L). A second dialysis, 2 days later, employed standard buffer throughout. RESULTS:We found a clearcut separation of blood pH and bicarbonate concentrations after 90 minutes of "isohydric dialysis" (pH = 7.37, bicarbonate = 22.4 mmol/L) and standard dialysis (pH = 7.49, bicarbonate = 29.0 mmol/L). Binding affinity varied widely among the 10 uremic retention solutes analyzed. Kynurenic acid (0.05 free), p-cresyl sulfate (0.12 free) and indoxyl sulfate (0.13 free) demonstrated the greatest degree of binding. Three solutes (indoxyl glucuronide, p-cresyl glucuronide, and phenyl glucuronide) were virtually unbound. Analysis of free and bound concentrations of uremic retention solutes confirmed our prediction that binding of solute is affected by pH. However, in a mixed models analysis, we found that the reduction in total uremic solute concentration during dialysis accounted for a greater proportion of the variation in free concentration, presumably an effect of saturation binding to albumin, than did the relatively small change in pH produced by isohydric dialysis. The effect of pH on binding appeared to be restricted to those solutes most highly protein-bound. The solutes most tightly bound exhibited the lowest dialyzer clearances. An increase in dialyzer clearance during isohydric and standard dialyses was statistically significant only for kynurenic acid. CONCLUSION:These findings provide evidence that the binding of uremic retention solutes is influenced by pH. The effect of reducing buffer bicarbonate concentration ("isohydric dialysis:"), though significant, was small but may be taken to suggest that further modification of dialysis technique that would expose blood to a greater decrease in pH would lead to a greater increase the free fraction of solute and enhance the efficacy of hemodialysis in the removal of highly protein-bound uremic retention solutes.